Key parameters and sensitivity analysis of lower limb muscle strength in young men with different gait patterns - Yifei Wang; Jianbo Sun; Xuesong Guo; Delong Dong; Chuankai Luan; Xiaolin Wang (PLoS ONE, 2025)
Objective To explore the functional characteristics and principal component differences of electromyography in different phases of the gait cycle, to provide key parameters for identifying a complete gait, and to provide a reference for joint moment solving in the lower limb. Methods Twenty young men were selected to measure the natural gait EMG of 14 muscles of the lower limb using VICON and NORAXON devices. Gait was classified into two categories according to the Niyogi S A classification, integral EMG differences were compared, and principal component analysis was performed on the differing muscles to calculate Cohen’s d values for significant differences and ΔIEMG values for non-significant differences. Results (1) Significant differences existed in the integral EMG of the left semitendinosus, right semitendinosus, right biceps femoris, and left gastrocnemius muscles, both lateral and medial. (2) Principal component analysis showed significant differences in the left semitendinosus for principal component five (P < 0.1, ES = 1.40); right biceps femoris for principal component three (ES = 0.63, 10%-30%); and left gastrocnemius medial for principal component four (P < 0.05, ES = 1.81, 40%-60%). The ΔIEMG% of the right semitendinosus principal components I-IV were 97.96%, 92.24%, 87.26%, and 75.08%, respectively; and the ΔIEMG% of the left gastrocnemius medial principal components I-IV were 90.95%, 75.08%, 96.37%, and 85.39%, respectively. Conclusion (1) Left semitendinosus, right semitendinosus, right biceps femoris, and left gastrocnemius can be used as the main muscles for gait recognition. (2) The left semitendinosus principal component V, the right biceps femoris principal component III, and the left gastrocnemius medial principal component IV are sensitive indicators for gait stage classification.